Life: perpetually perishing, perpetually regenerated - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 1998)
...green pastures ... through the valley of the shadow of death Psalm 23. 1. The Struggle for Survival. 2. The Evolution of Pain. 3. Regeneration and Redemption. 4. A Cruciform Creation.
Lecture 3 was presented October 10, 1998 at the Carl Howie Lectures, Watts Chapel, Union-PSCE, Howie Center for Science, Art, and Theology, Union Theological Seminary, Richmond, Virginia.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.